Utilization of Reflex Testing for Direct Bilirubin in the Early Recognition of Biliary Atresia. (6th January 2020) - Lam, Leo; Musaad, Samarina; Kyle, Campbell; Mouat, Stephen
Abstract: BACKGROUND: Delayed diagnosis of biliary atresia is an important cause of pediatric end-stage liver failure and liver transplantation. We sought to determine whether direct bilirubin is underutilized by retrospectively reviewing patients with biliary atresia. Further, we aimed to determine the role of reflex testing for direct bilirubin in patients suspected for jaundice. METHODS: The time intervals between total bilirubin and direct bilirubin measurements were retrospectively reviewed in patients with biliary atresia. We also audited the results of two major laboratories that had implemented reflex testing for direct bilirubin. We evaluated the clinical impact and cost of reflex testing in infants with increased direct bilirubin (>1.5 mg/dL; >25 μmol/L). RESULTS: In patients with known biliary atresia, an isolated total bilirubin measurement preceded direct bilirubin measurement in 46% (40/87) of patients; with a median delay of 19 days (interquartile range 3–44 days). In the community setting, direct bilirubin had a higher clinical specificity for biliary atresia than in the hospital setting. Reporting direct bilirubin results in 1591 infants younger than 2 weeks of age in the community was associated with three admissions to the hospital, one of whom was diagnosed with biliary atresia. The cost for the two laboratories for direct-bilirubin testing was estimated at US$3200 (NZ$4600) for each newly diagnosed case of biliary atresia. CONCLUSIONS: We identified underutilization of direct bilirubin as a cause of delay in the recognition of biliary atresia and show that reflex testing for direct bilirubin in jaundiced infants is a cost-effective solution.